The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5036750
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapped holes in BaTiO3

Abstract: The behavior of holes in the valence band of BaTiO 3 is investigated using hybrid densityfunctional calculations. We find that holes tend to self-trap, localizing on individual O atoms and causing local lattice distortions, forming small hole-polarons. This takes place even in the absence of intrinsic defects or impurities. The self-trapped hole (STH) is more energetically favorable than the delocalized hole in the valence band. The calculated emission peak energy corresponding to the recombination of a conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…O is not increased so high and consequently imposes the lower limit of the Fermi level. Furthermore, we have found the self-trapped hole (STH) is also stable by 0.25 eV and 0.29 eV in the R and C D phases, respectively, which are close to the previously reported self-trapping energy of 0.2 eV in highly symmetric cubic BTO [42]. Thus, it seems difficult to achieve the p-type BTO even if shallow acceptor dopants exist and V O is well suppressed by a growth technique.…”
Section: O and Ti −supporting
confidence: 88%
See 1 more Smart Citation
“…O is not increased so high and consequently imposes the lower limit of the Fermi level. Furthermore, we have found the self-trapped hole (STH) is also stable by 0.25 eV and 0.29 eV in the R and C D phases, respectively, which are close to the previously reported self-trapping energy of 0.2 eV in highly symmetric cubic BTO [42]. Thus, it seems difficult to achieve the p-type BTO even if shallow acceptor dopants exist and V O is well suppressed by a growth technique.…”
Section: O and Ti −supporting
confidence: 88%
“…Calculated recombination energies of the electron polarons (Ti − Ti , V + O , V 0 O , H 0 O , and H 0 i ) with a hole at the VBM are 2.1-2.3 eV and 2.0-2.3 eV for the R and C D models, respectively, which are close to the experimental values of 2.4-2.5 eV [7][8][9]. Recently, Traiwattanapong et al have reported recombination energy of a STH and an electron at the CBM to be 2.17 eV [42], which is close to our calculated 2.33 and 2.04 eV in the R and C D phases, respectively. Therefore, the electron polarons, hole polarons, or both may be the origin of the green luminescences in BTO.…”
Section: O and Ti −supporting
confidence: 76%
“…One could expect intuitively holes localized on O ions nearest to the cation what happens often for the hole polarons in oxides, e.g. MgO:Li [35] and perovskites [13,36]. In addition, analysis of the electronic density of states (DOS) for (Ce,Tb)O2 ( fig.…”
Section: A Comparison Of Parent Oxides and Delocalization Of Holesmentioning
confidence: 99%
“…Examples of STHs are found in TiO 2 , β-Ga 2 O 3 , CdWO 4 , and Y 3 Al 5 O 12 crystals [3][4][5][6] and also amorphous SiO 2 [7,8]. Firstprinciples calculations have predicted that STHs will be stable at low temperature in SrTiO 3 and BaTiO 3 crystals [9,10]. Self-trapping occurs in a crystal when the lattice surrounding the hole relaxes and forms a shallow potential well.…”
Section: Introductionmentioning
confidence: 99%